Norges kirker - Nyborg, Ebbe (Hikuin, 2006)
Norwegian Churches By Ebbe Nyborg Norwegian churches are still in use, even far north beyond the Arctic Circle. But they are also monuments of Christianity down through the ages. They are excellent cultural monuments. Here of course we consider especially the older churches, the stave churches, Norway’s unique contribution to the European cultural heritage, the stone churches and their ruins from the Middle Ages and the wooden churches from the 17th-18th centuries. As far as proportions are concerned, there is only one single Norwegian church, Nidarosdomen, to match the larger West European cathedrals of the Middle Ages. This church, however, represents the whole of Scandinavia with its exquisite architecture and sculptures, the origins of which are still a bit of a research mystery. Neither can it be said that the old, Norwegian churches excel in number and by this make an impression on the countryside. This is due to the fact that far too many churches have been demolished. As we know today there are only twenty-six listed stave churches left out of the hundreds once to be found in the valleys. The churches are key factors in our culture. There can never be too much co-operation and friendship. He we are to celebrate and dwell upon the fertile Nordic co-operation, which thrives in church research, and which for a long time has manifested itself by research gatherings such as this in Søgne. Just think, that we from all Scandinavia know each other personally in our field of work and can learn from each other, be inspired by each other and by positive criticism. It is not only a personal happiness and enrichment. Our co-operation gives an invaluable encouragement both in connection to our own work and challenges, and when we are to enter the international scene and draw attention to the delights of the Scandinavian world.